2005
DOI: 10.1056/nejmoa042683
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis Caused by Community-Associated Methicillin-ResistantStaphylococcus aureusin Los Angeles

Abstract: Necrotizing fasciitis caused by community-associated MRSA is an emerging clinical entity. In areas in which community-associated MRSA infection is endemic, empirical treatment of suspected necrotizing fasciitis should include antibiotics predictably active against this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
604
6
22

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 967 publications
(649 citation statements)
references
References 56 publications
17
604
6
22
Order By: Relevance
“…Analysis of representative strains demonstrated that virulence was considerably increased in the lineage that comprises USA300 compared with the other CC8 MRSA lineages. This is consistent with the reported potential of USA300 to cause severe and widespread disease (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of representative strains demonstrated that virulence was considerably increased in the lineage that comprises USA300 compared with the other CC8 MRSA lineages. This is consistent with the reported potential of USA300 to cause severe and widespread disease (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…Type I ACME has been postulated to contribute to growth and survival of USA300 within the host, and promote colonization of the human skin [26]. ACME is integrated downstream of type IV SCCmec (Figure 2), utilizing the same cassette chromosome recombinases A and B (ccrAB) contained with SCCmec for mobilization and transfer [15][16][17][18][19][20][21][22][23][24]34]. Type I ACME is a distinctive genetic feature of the USA300 pandemic clone [26,34,35], although ACME-like elements have been detected in sporadic MRSA [32][33][34].…”
Section: Unique Genomic Contentsmentioning
confidence: 99%
“…Not seen before the year 2000, USA300 is now pandemic in communities across 38 U.S. states, Canada, and 9 European countries [11]. The pandemic clone USA300 has been implicated in unusually severe human diseases, including endocarditis, pneumonia, sepsis, and necrotizing fasciitis [16,17,29]. Remarkably, the introduction of USA300 into a new geographic area has often been associated with the displacement of locally endemic CA-MRSA strains belonging to ST1, ST30, ST59 and ST80 clonal lineages [22,23,32,33].…”
Section: Community-associated Clones Of Mrsamentioning
confidence: 99%
“…HA-MRSA strains, which have circulated in healthcare settings for decades, are associated with pneumonia, bacteraemia and other invasive infections in patients with co-morbid illnesses in healthcare facilities (Mulligan et al, 1993). While CA-MRSA usually causes skin and soft tissue infections in otherwise healthy individuals (Watkins et al, 2012), more severe, invasive diseases may occur and can include necrotizing pneumonia (CDC, 2007;Kwong et al, 2012), pyomyositis and necrotizing fasciitis (Miller et al, 2005;Pannaraj et al, 2006), sepsis (Fortunov et al, 2006), osteomyelitis (Bocchini et al, 2006) or septic arthritis (Arnold et al, 2006).…”
Section: Introductionmentioning
confidence: 99%